Parkinsonia aculeata (Caesalpineaceae) improves high-fat diet-induced insulin resistance in mice through the enhancement of insulin signaling and mitochondrial biogenesis - Araújo, Tiago Gomes; De Oliveira, Alexandre Gabarra [UNESP]; Vecina, Juliana Falcato; Marin, Rodrigo Miguel; Franco, Eryvelton Souza; Abdalla Saad, Mario J.; De Sousa Maia, Maria Bernadete (Elsevier, 2016)
Ethnopharmacological relevance The search for natural agents that minimize obesity-associated disorders is receiving special attention. Parkinsonia aculeata L. (Caesalpineaceae) has long been used in Brazil as a hypoglycaemic herbal medicine, without any scientific basis. Aims of the study In this context, we aimed to use molecular and physiological methods to study the effect of a hydroethanolic extract partitioned with ethyl acetate from the aerial parts of Parkinsonia aculeata (HEPa/EtOAc) on insulin resistance in a mouse model of diet-induced obesity (DIO). Material and methods Firstly, C57BL/6J mice were fed either with standard rodent chow diet or a high-fat diet (HFD) for 12 consecutive weeks. Then, the animals were treated with HEPa/EtOAc at two doses (125 and 250 mg/kg/day) or metformin (200 mg/kg/day) for 16 days. At the end of the experiment, body weight, fat pad weight, fasting serum glucose (FSG), insulin (FSI) and leptin were measured. Homeostasis Model Assessment for Insulin Resistance (HOMA-IR) was also calculated. Glucose, insulin and pyruvate tolerance tests were performed. The expression and phosphorylation of IRβtyr, Aktser473, AMPKα and PGC1α in liver, muscle and adipose tissue were determined by Western blot analyses. Results Herein we demonstrate for the first time an improvement in insulin resistance following HEPa/EtOAc administration in obese mice, as shown by increased glucose, insulin and pyruvate tolerance, as well as an improvement in FSG, FSI, HOMA-IR and circulating leptin levels, which together are in part due to enhancement of the insulin signaling pathway in its main target tissues. Surprisingly, the increase in activation of the AMPKα-PGC1-α axis by HEPa/EtOAc was similar to that produced by metformin treatment in the liver and muscle tissues. Conclusion In conclusion, P. aculeata appears to be a source of therapeutic agent against obesity-related complications.
Keywords: AMPKα; Herbal medicine; Insulin resistance; Mitochondrial biogenesis; Obesity; Parkinsonia aculeata